The Structural Design and Aerodynamics Analysis for a Hybrid VTOL Fixed-Wing Drone for Parcel Delivery Applications - Chakraverty, Seyhrvin; Zulkafli, Mohd Fadhli; Pairan, Mohammad Fahmi; Mohd Shakir See, Mohamad Nadjmi; Mahmud, Izzat Khair (Progress in Aerospace and Aviation Technology, 2022)
A number of companies are experimenting with multicopter drones to deliver items to clients. Because electric planes have a restricted range, their flight range is usually constrained. However, if propelled by gasoline, electric multicopters drones can only travel a short distance because to high power consumption and noise difficulties. Despite their lower aerodynamic efficiency than fixed-wing aircraft, multicopters’ ability to do vertical take-off and landing (VTOL) makes them ideal delivery vehicles. Hybrid fixed-wing VTOL systems with a tilting system that alters the flight mode could be an upgrade. The goal is to effectively manufacture a fixed-wing drone with appropriate structural design and a functional tilting mechanism that can take off vertically. SolidWorks and SIMNET aero were the two approaches used throughout the design software. The drone’s aerodynamic qualities were investigated in order to better understand its behaviour, such as range of flight at a given altitude, stall speed, and maximum lift created, in order to determine the maximum parcel weight the drone can carry. The drone was built using SolidWorks 3D-Solid modelling and SIMNET aero design software. Because it is lightweight and sturdy, the tilting mechanism is 3D printed utilising (Polylactic Acid, PLA). The in-fill can also be changed to modify the strength. Following manufacturing, many test flights were done to investigate the drone’s genuine behaviour and improve its performance. The drone’s theoretical stall speed was found to be 11.43 m/s at free load and 12.74 m/s with a maximum payload of 500g. For maximum glide, the range calculated 1.2 kilometres. During test flights, the drone yaws to the left at 63.43 degrees at 4.879 degrees per second at 50% throttle. It slanted to the front nose down with a weight of 516 g while support was given at the tip of the left wing. The pitch rate was 2.5 degrees per second without payload and 3.12 degrees per second with the 516g payload. Experimental results that are similar to theoretical outcomes would be obtained with further design and calibration improvements.